Composition of nests constructed by species in the Motacillidae, Sylviidae and Prunellidae. Issue 1 (February 2022) - Dickinson, Amy M; Locke, Emily; Gray, Liberty A; Bennett, Sophie L; Biddle, Lucia E; Goodman, Adrian M; Deeming, Denis Charles
Bird nests can be complex bio-engineered structures constructed from a range of materials to provide a site for incubation, and in many species chick rearing. Reports of the materials used in nest walls and cup linings are typically qualitative and do not assist in understanding the functional properties of the structure as a whole. This paper provides size and composition data for nests from four species of the Motacillidae family: the meadow pipit ( Anthus pratensis ), pied wagtail ( Motacilla alba ), grey wagtail ( Motacilla cinerea ), and the yellow wagtail ( Motacilla flava ), three species of the Sylviidae family: willow warbler ( Phylloscopus trochilus ), Eurasian reed warbler ( Acrocephalus scirpaceus ) and Eurasian blackcap ( Sylvia atricapilla ), and the dunnock ( Prunella modularis ) of the Prunellidae family. Three hypotheses were tested: do nest dimensions correlate with body mass? Is it possible to distinguish among species based on their nest composition; and for individual species? Is it possible to distinguish between the cup lining and outer nest wall based on the materials used in construction? Nest composition and size varied among species although the degree of intra-specific variation was different. Size of a nest was unrelated to average female adult body mass. Composition relied on similar types of materials but in differing quantities between species. It was possible to distinguish among species in terms of nest construction, and between the cup lining and the outer nest, on the basis of at least one of the component materials. By providing quantitative data on composition, it may be possible in the future to understand better the structural, insulative and hydrological properties of the nest. Such information will be invaluable as we begin to develop an understanding of the factors that have driven evolution of nest architecture.